Industrial robots - Anishchenko, M. V.; Asmolova, L. V.; Semikov, O. V. (Національний технічний університет "Харківський політехнічний інститут", 2026)
In this training manual: the history and development trends of robotics, issues concern- ing the socio-economic efficiency of employing robotic systems and safety practices in robot- ics are examined; fundamental concepts, definitions, and a classification of robotics are pre- sented; kinematic diagrams, principal 9components and assemblies of industrial robots, math- ematical descriptions of kinematic schemes and drives, methods and programming languages, as well as algorithms for programmed, adaptive, and intelligent control are considered; the specific features of applying robotic systems in various industries are outlined. This is intended for students enrolled in the "Electric Drive, Mechatronics and Robotics" educational program, first (bachelor's) level of higher education, in the specialty G3 "Electrical Engineering", as well as for students of other educational programs.
Keywords: training manual; industrial robots; robotics development; prehistory of robotics; bebefits of robots; robot terminology